Larval Survey of Dengue Endemic Area In Samarinda, East Kalimantan, Indonesia Guide to determine of risk containers - M Rasyid Ridha; Sri Sulasmi (International Journal of Public Health Science (IJPHS), 2022)
Dengue hemorrhagic fever (DHF) has been reported in Indonesia since1968, the cases tend to increase and spread every year. In 2015-2019 almost all districts in Indonesia had dengue cases. This study aimed to determine the value of the entomological index and its relationship with the treatment of various types of containers, and spatial epidemiology. A larval survey was conducted to determine the presence of larvae in water containers. Logistic regression and spatial data analysis were performed to see the distribution and make buffer area map of Aedes spreading risk. The types of containers observed in this study were water tubs, drums, buckets, refrigerator containers, dispenser containers, and other categories. There were 221 containers found containing Aedes larvae. Container types affected the presence of larvae with adjusted ORs of 2.779 (95% CI: 1.441-5.360) on buckets, 9.812 (95% CI: 1.249-77.051) on refrigerator holders, and 0.301 ( 95% CI: 0.147-0.617) on dispenser holders, while the other variables were constant. The spatial analysis found that many houses are at risk of dengue transmission within a radius of 100m. The discovery of containers as potential breeding sites for Aedes provides a chance for an increase in dengue cases in Samarinda.